Wawasan Kebangsaan sebagai Cara Pandang Masyarakat Mereduksi Pemilih Apatis dalam Menyongsong Pemilu yang Demokratris dan Pastisipatif - Lestari, Sulistyani Eka; Mangkunegara, RM. Armaya; Nugroho, Aguk; Muhari, Muhari; Harysart, Vivin Astharyna (Neolectura, 2024)
Indonesia's diverse society, as the Unitary State of the Republic of Indonesia (NKRI), has the potential to trigger division if not managed properly. This report discusses the importance of national insight as a perspective for reducing voter apathy ahead of the 2024 elections. National insight here includes understanding national identity and unity based on Pancasila, Bhinneka Tunggal Ika, NKRI, and the 1945 Constitution. Voter apathy and the potential for abstention in elections are often triggered by political rhetoric and campaigns that rely on agitation and propaganda. Therefore, socialization and education are needed to increase voter participation actively and rationally. Through community service activities by lecturers from the Faculty of Law, Sunan Bonang University, national insight socialization, and education were carried out in Saringembat Village, Singgahan District, Tuban Regency. This activity aims to support the government in successfully conducting the 2024 elections by enhancing nationalism and voter participation. The methods used include participatory and descriptive approaches, with presentations on national insight and election simulations to realize fair and democratic elections